"Algo grande, admirable, divino": capacidad de admiración inteligente y creyente en el Contra Faustum de san Agustín = Abweichender Titel: "Something Great, Admirable, Divine" : The Capacity for Intelligent and Faithful Admiration in Saint Augustine's Contra Faustum - D'Andrea, Bruno ca. ca. 21. Jh. (Cauriensia, 2025)
In this article we would like to present, in the context of a christological dispute between manichaean Faustus and Augustine of Hippo, how Augustine came to describe the concept of miracle, together with that of nature, to affirm the way in which man must place himself before the power of God, which is not capricious, but manifestative of his being, which, in turn, corresponds to truth. In fact, God's power is revealed in the wisdom and beauty of the laws that govern the creaturely cosmos, before which man can only position himself and express himself in an approximate and almost always inadequate manner. Ultimately, man enjoys the capacity for believing wonder, which is born of the acceptance of the God who reveals Himself in the incarnate Word.